Zulma Ageitos de Castellanos: Publications and status of described taxa - Signorelli, Javier H.; Urteaga, Diego; Teso, Valeria (Zootaxa, 2015)
Zulma Ageitos de Castellanos was an Argentinian malacologist working in the “Facultad de Ciencias Naturales y Museo” at La Plata University where she taught invertebrate zoology between 1947 and 1990. Her scientific publications are listed in chronological order. Described genus-group and species-group taxa are listed. Information about the type locality and type material, and taxonomic remarks are also provided. Finally, type material of all described taxa was requested and, when located, illustrated.